54.5k views
0 votes
H(n)=4n+ 4 find h (-3)

2 Answers

4 votes

Explanation:

h(n)=4n+ 4 find h (-3)

h(-3)=4(-3)+4

=-12+4

=--8

User Wolfgang Jeltsch
by
5.5k points
4 votes

Answer: -8

Step-by-step explanation: h(n) = 4n + 4 means that

if we put an n into our function, a 4n + 4 comes out.

So here, we're putting a -3 into our function which means that

a 4(-3) + 4 comes out which simplifies to -12 + 4 or -8.

So h(-3) = -8 or the value of the function at -3 equals -8.

User David Faure
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.